Readiness for Village Apparatus in Tourist Destinations Competitiveness of Tanjung Lesung SEZ, Tanjung Jaya Village, Panimbang District, Pandenglang - Felix Goenadhi (AIBPM Publisher, 2022)
Special Economic Zones (SEZ) Tourism in Tanjung Lesung is a distinct advantage because it can provide promising business development potential. However, this potential is less than optimal due to the condition of village officials to develop tourist villages in the vicinity, or SEZ supporting areas, namely Tanjung Jaya Village, not running optimally. This research uses a qualitative method by conducting a Focus Group Discussion (FGD) with the Tanjung Jaya Village Head, Panimbang District Secretary, the POKDARWIS Chair, and several other village officials who can make the supporting area better. The results obtained based on the FGD are by developing Human Resources (HR) for Micro, Small and Medium Enterprises (MSMEs) and making the people of Tanjung Jaya Village aware of the need for tourism in the SEZ supporting area. The other result was a lack of training for staff or owners of MSMEs. The program that will be provided in the future is HR training on soft skills to POKDARWIS members, Tourism Village Managers, and Banten West Java (BWJ) as a Company Social Responsibility (CSR) program. So that later the POKDARWIS, Tourism Village Managers can provide input or explanations and retrain the people of Tanjung Jaya Village.